The Handbook of Multilingualism, Identity, and Language Endangerment in Africa
103 illus., 78 illus. in color. eReference.
Keywords: This handbook addresses the interrelatedness of nationalism, identity, language, linguistics, and multilingualism in an African context. It covers multilingualism, language and identity, language endangerment, language shift, language maintenance, language contact, diglossia, language decline, language death, language vitality, and much more in, linguistically, one of the richest regions on earth. The variety of alphabets and oral traditions immersed in folklore, made more linguistically complex through issues of inter-borders, and the long history of foreign intrusions and colonialism, has meant a collision of identities and linguistic peculiarities. This book considers these facets in relation to language endangerment in numerous geographies within the African continent. It confronts these questions under the rubric of multilingualism, linguistic geography, and a panoply of other sub-studies. By investigating a multitude of topics around the themes of multilingualism, identity, and language endangerment in Africa, this volume brings together these dimensions to showcase interdisciplinary research in studies of African languages and linguistics. Relevant to applied linguists, socio-linguists, cultural linguistics, language teachers, anthropologists, and scholars in African cultural studies more broadly, this is a vital, urgent text challenging language, and identity, endangerment.